Heterogeneity of Clostridioides difficile asymptomatic colonization prevalence: a systematic review and meta-analysis - Daniel De-la-Rosa-Martínez; Rodrigo Villaseñor-Echavarri; Diana Vilar-Compte; Virna Mosqueda-Larrauri; Paola Zinser-Peniche; Seth Blumberg (Gut Pathogens)
Abstract Background Asymptomatic carriers significantly influence the transmission dynamics of C. difficile. This study aimed to assess the prevalence of toxigenic C. difficile asymptomatic colonization (tCDAC) and investigate its heterogeneity across different populations. We searched MEDLINE, Web of Science, and Scopus for articles published between 2000 and 2023 on tCDAC. Studies including asymptomatic adults with laboratory-confirmed tCDAC were eligible. We performed a random-effects meta-analysis to estimate the pooled prevalence by clinical characteristics, settings, and geographic areas. In addition, we used outlier analyses and meta-regression to explore sources of prevalence variability. Results Fifty-one studies involving 39,447 patients were included. The tCDAC prevalence ranged from 0.5 to 51.5%. Among pooled estimates, a high prevalence was observed in patients with cystic fibrosis, outbreak settings, and cancer patients, whereas the lowest rates were found in healthy individuals and healthcare workers. Similar colonization rates were observed between admitted and hospitalized patients. Our meta-regression analysis revealed lower rates in healthy individuals and higher rates in cystic fibrosis patients and studies from North America. Additionally, compared with that among healthy individuals, the prevalence significantly increased by 15–47% among different populations and settings. Conclusion Our study revealed that tCDAC is a common phenomenon. We found high prevalence estimates that showed significant variability across populations. This heterogeneity could be partially explained by population characteristics and settings, supporting their role in the pathogenesis and burden of this disease. This highlights the need to identify high-risk groups to improve infection control strategies, decrease transmission dynamics, and better understand the natural history of this disease.